Applying a Multiple Convergent Process in Achieving a Successful of New Product Developmen - Masyhuri, Muhammad (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2022)
New Product Development (NPD) is critical for companies to improve their business results. However, few companies can benefit from such a process because it is difficult to determine how and which NPD processes should be designed to develop a leading-edge product. The objective of this study is to find out the appropriate and best approach for implementing an NPD process in a company. The Multiple Convergent Process (MCP) framework model is applied by borrowing the framework model of (Baker & Hart, 2007). The objective of the MCP framework model is to apply a parallel mechanism of NPD phases to work towards the same point or common outcome without delaying the next phase. This study applies a descriptive research method by describing the steps of the MCP model and using literature reviews. Fifty-two publications from 1990 to 2018 were reviewed. Major and related topics such as NPD, innovation, multiple convergent points, idea generation - evaluation - concept and selection, and factors for successful NPD were considered.